Development of a nanogel-based nasal vaccine as a novel antigen delivery system. (2nd December 2017) - Nakahashi-Ouchida, Rika; Yuki, Yoshikazu; Kiyono, Hiroshi
ABSTRACT: Introduction : Nasal vaccination is one of the most effective immunization methods because it can induce effective antigen-specific immune responses not only at the mucosal site of administration but also at distant mucosal surfaces, as well as in the systemic compartment. Based on this advantage, many nasal vaccines are being developed and some have been licensed and marketed for clinical use. However, some have been withdrawn because of unacceptable adverse events such as inactivated influenza vaccine administrated with a heat-labile enterotoxin of Escherichia coli as an adjuvant. Thus, it is important to consider both the efficacy and safety of nasal vaccines. Areas covered : This review describes the benefits of cholesteryl group–bearing pullulan (CHP) nanogels for nasal vaccine delivery and vaccine development identified on Pubmed database with the term 'Nanogel-based nasal vaccine'. Expert commentary : CHP nanogels have been developed as novel drug delivery system, and a cationic CHP nanogels have been demonstrated to induce effective immunity as a nasal vaccine antigen carrier. Since vaccine antigens incorporated into CHP nanogels have exhibited no brain deposition after nasal administration in mice and nonhuman primates, the vaccine seems safe, and could be a promising new delivery system.